ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA SEBELUM DAN SAAT PANDEMI COVID-19 - Ikbal Hallan Ibrahim; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study was conducted to determine differences in the financial performance of cigarette sub-sector companies listed on the Indonesia Stock Exchange before and during the COVID-19 pandemic. This type of research is quantitative with a comparative study using purposive sampling method. The data used in this research is secondary data. Data was processed by paired sample t-test. From the results of data processing, it shows that there is no significant difference in the Quick Ratio of cigarette sub-sector companies listed on the IDX between before and during the COVID-19 pandemic. This is indicated by a significant t value of 0.873 > 0.05, there is no significant difference in the Debt to Equity Ratio of cigarette subsector companies listed on the IDX between before and during the COVID-19 pandemic. This is indicated by a significant t value of 0.880 > 0.05, there is no significant difference in the Return on Equity of cigarette sub-sector companies listed on the IDX between before and during the COVID-19 pandemic. This is indicated by a significant t value of 0.209 > 0.05, there is no significant difference in the Total Asset Turnover of cigarette subsector companies listed on the IDX between before and during the COVID-19 pandemic. This is indicated by a significant value of 0.064 > 0.05 Keywords: Covid-19, Quick ratio, Debt to Equity Ratio, Return On Equity, Total asset Turnover.